Evaluation of Rhizosphere Bacterial Antagonists against Ralstonia solanacearum Causing Tomato (Lycopersicon esculentum) Wilt in Central Ethiopia - Tsigie Gashaw; Baye Sitotaw; Solomon Yilma (International Journal of Agronomy)
Tomato (Lycopersicon esculentum) is one of the most commonly grown vegetables in Ethiopia. However, diseases such as bacterial wilt caused by Ralstonia solanacearum have been limiting the production. The rhizosphere is an important source of antagonistic bacteria against soilborne pathogens. This study aimed to investigate the antagonistic potential of rhizosphere bacteria against R. solanacearum in vitro. The pathogen was isolated from wilted tomato plants and tested for hypersensitivity reactions to ascertain the virulent R. solanacearum. Antagonistic rhizobacteria were also isolated from the rhizosphere of healthy tomatoes. Isolates were identified based on cultural characteristics and biochemical tests. The antagonistic effect of rhizobacteria against R. solanacearum was tested in vitro. In addition, the growth of rhizobacterial isolates was determined at different levels of temperature, pH, and NaCl. Of the 36 randomly collected colonies, 7 isolates were identified as Ralstonia spp., all of which were grouped under R. solanacearum biovar III. Similarly, 57 rhizobacteria were isolated, and only 14 had shown antagonistic effects against R. solanacearum. The antagonistic rhizobacteria were identified as Pseudomonas or Bacillus species. Significantly higher (p ≤ 0.05) antagonistic activity (14.66 mm inhibition zone) was recorded by Pseudomonas isolate (P6) than recorded by the rest of the isolates and the positive control. Nine rhizobacterial isolates (out of 14) demonstrated higher or equal inhibition zones recorded by the positive controls. All isolates grew at temperatures ranging 15–45°C, pH 5–9, and 2–5% NaCl. The Bacillus spp. grew at all conditions except at pH 3, showing that they can tolerate wide range of growth conditions. The results of this study showed the presence of potential antagonistic bacteria against R. solanacearum in the study area, which can be used for the control of bacterial wilt of tomato as an alternative management option. Further study is required to determine the efficacy at greenhouse and field conditions.